Optimization Reaction Conditions for synthesis of 1,1’-Bis- (3,5-Dimethyl-4-Hydrocyphenyl) Cyclohexane - Garchar, H.H.; Parsania, P.H. (Asian Journal of Chemistry, 2010)
The optimization conditions for the reaction between cyclohexanone (0.05 mol) and 2,6-dimethyl phenol (0.1 mol) in the presence of varying mixtures of hydrochloric acid and acetic acid (2 : 1 v/v) were investigated at four different temperatures, viz., 40º,50º, 60º and 70ºC. The optimum reation conditions such as temperature, catalyst concentration and time have been investigated for obtaining yields greater than 80%. The purity and structure of the 1,1´-bis(3,5-dimethyl-4-hydroxyphenyl) cyclohexane is supported by TLC and HPLC and IR, 1H NMR and 13C NMR data.